A Retrotransposon Insertion in GhMML3_D12 Is Likely Responsible for the Lintless Locus li3 of Tetraploid Cotton - Chen, Wei; Li, Yan; Zhu, Shouhong; Fang, Shengtao; Zhao, Lanjie; Guo, Yan; Wang, Junyi; Yuan, Li; Lu, Youjun; Liu, Fang; Yao, Jinbo; Zhang, Yongshan (Frontiers in Plant Science, 2020)
Cotton (Gossypium) seed fibers can be divided into lint (long) or fuzz (very short).Using fiberless (fuzzless-lintless) mutants, the lint initiation gene Li3 was identified by map-based cloning. The gene is an R2R3 MYB transcription factor located on chromosome D12 (GhMML3_D12). Sequence analysis revealed that li3 is a loss-offunction allele containing a retrotransposon insertion in the second exon that completely blocks the gene's expression. The genetic loci n2 and n3 underlying the recessive fuzzless phenotype in G. hirsutum were also mapped. The genomic location of n3 overlapped with that of the dominant fuzzless locus N1, and n3 appeared to be a loss-offunction allele caused by an SNP mutation in the coding region of GhMML3_A12. The n2 allele was found to be co-located with li3 and originated from G. babardense. n2 and li3 are possibly the multiple alleles of the GhMML3_D12 gene. Genetic analysis showed that Li3 and N3 are a pair of homologous loci with additive effects for the initiation of fibers (fuzz or lint). In addition, another locus showing an inhibitory effect on the expression of GhMML3 was identified. These findings provide new and contrasting information about the genetic factors affecting the initiation of fibers in cotton.